The Relationship between the Knowledge Level of PUS Mothers and the Use of Long-Term Contraceptive Methods (LTCM) in the Basarang Community Health Center Work Area - Betrisia Betrisia; Widia Shofa Ilmiah (STIKES Columbia Asia Medan, 2025)
Long-acting contraceptive methods (LACMs/MKJP) are effective family planning options for controlling fertility and improving maternal health. However, the utilization of LACMs among women of reproductive age remains relatively low, which may be influenced by their level of knowledge. This study aimed to examine the relationship between women’s knowledge levels and the utilization of long-acting contraceptive methods in the working area of UPT Puskesmas Basarang. A quantitative study with a cross-sectional design was conducted involving 58 women of reproductive age selected using purposive sampling. Data were collected using a structured questionnaire to assess knowledge levels and contraceptive use, and analyzed using the Kendall’s tau-b correlation test. The results showed that more than half of respondents had good knowledge of LACMs, yet only 39.7% reported using these methods. Bivariate analysis revealed a statistically significant relationship between knowledge level and LACM utilization (p = 0.012). The study concludes that knowledge is significantly associated with the use of long-acting contraceptive methods, although other factors may also influence decision-making. Strengthening education and counseling interventions is essential to improve informed contraceptive choices and increase the utilization of long-acting contraceptive methods.